Poligami di Tunisia; Studi Alasan Pelarangan Poligami - Ali Trigiyatno (Jurnal Hikmatuna, 2017)
The prohibition of polygamy in Tunisia, a country that is 98% Muslim population surprised many. On the one hand he was hailed as a success for this group wants ban on polygamy, but on the other hand he also criticized by many scholars as a legal product that is not syar'i. The prohibition of polygamy in Tunisia backdrop of internal and external factors. Internal factors such as the reinterpretation of Surat an-Nisa` paragraph 3 is associated paragraph 129. In addition, there is also a desire to lift and align the position of men and women. Average external factors such as the influence of the French legal system that once colonized Tunisia. It also factors figure Habib Bourguiba who was educated Western (French) were secular and rule with an authoritarian. The prohibition of polygamy have recently started being sued by a group of people who want a return to Islamic law.